2007
DOI: 10.1080/00268970701218704
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical spectroscopy study of theX3Σand theA3Π states of the C2S radical

Abstract: The spin-rovibronic levels for the X 3 Σ − , A 3 Π electronic system of C 2 S are calculated variationally, using ab initio potential energy surfaces and taking into account the non-adiabatic coupling between the two states. The energies of selected levels with Σ and Π vibronic symmetry, up to ∼ 16500 cm −1 , are reported and compared with available experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
4
2
0
Order By: Relevance
“…The 3 ⌸ 2 and 3 ⌸ 1 components of 3 are found to be 807 and 936 cm −1 above the A 3 ⌸ 2 ground state, respectively. These values are slightly larger than the 788 and 913 cm −1 calculated by Tarroni et al 9 The position of both 1 spin-orbit multiplets are in excellent agreement with the previous observations ͑see…”
Section: B Ccs −supporting
confidence: 93%
See 4 more Smart Citations
“…The 3 ⌸ 2 and 3 ⌸ 1 components of 3 are found to be 807 and 936 cm −1 above the A 3 ⌸ 2 ground state, respectively. These values are slightly larger than the 788 and 913 cm −1 calculated by Tarroni et al 9 The position of both 1 spin-orbit multiplets are in excellent agreement with the previous observations ͑see…”
Section: B Ccs −supporting
confidence: 93%
“…Peaks U and V are separated by 133 cm −1 and are assigned to the 3 ⌸ 2 and 3 ⌸ 1 spin-orbit components of the A 3 ⌸ state origin transition. This splitting is in excellent agreement with calculations by Tarroni et al 9 The 3 ⌸ 0 state is not observed because a photodetachment transition from a 2 ⌸ 3/2 anion state to a 3 ⌸ 0 neutral state requires a spin-flip which is nominally forbidden. The two remaining doublets are thus assigned to vibrations belonging to the same two spin-orbit states.…”
Section: B Ccs −supporting
confidence: 90%
See 3 more Smart Citations